An investigation of the marketing mix factors influencing the purchasing behavior of Thai hair salon owners regarding hair color products - Kuyram, Ngamta (RMUTSB ACADEMIC JOURNAL, 2013)
The objective of this study was to investigate the marketing mix factors influencing the purchasing behavior of Thai hair salon owners regarding hair color products. The participants of this study were Thai hair salon owners who have run their business over one year, and their salons are located in Pathumwan, Bangrak, Sathon, and Wattana districts of Bangkok. The research instrument was a questionnaire. The questionnaire was divided into two parts: (1) the general information of the participants, and (2) the influencing factors based on the marketing mix. Copies of questionnaires were distributed directly to the participants, and 100 copies were returned. The obtained data were analyzed by using mean scores and standard deviation. The results showed that all 7P’s of the marketing mix factors: product, price, place, promotion, people, process, and physical evidence influenced the purchasing behavior of the owners of large, medium-sized and small hair salons. However, each business size gave important differences in prioritizing ‘P.’ The owners of large hair salon prioritized product followed by physical evidence, process, price, place, people, and promotion, respectively. As for the owners of medium-sized salon, they prioritized product followed by people, process, price, place, promotion, and physical evidence, respectively while the owners of small hair salon prioritized product followed by people, process, price, promotion, physical evidence, and place, respectively